2019
DOI: 10.1051/0004-6361/201936369
|View full text |Cite
|
Sign up to set email alerts
|

Study of the spatial association between an active region jet and a nonthermal type III radio burst

Abstract: Aims. We aim to investigate the spatial location of the source of an active region (AR) jet and its relation with associated nonthermal type III radio emission. Methods. An emission measure (EM) method was used to study the thermodynamic nature of the AR jet. The nonthermal type III radio burst observed at meterwavelength was studied using the Murchison Widefield Array (MWA) radio imaging and spectroscopic data. The local configuration of the magnetic field and the connectivity of the source region of the jet … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 45 publications
1
13
0
Order By: Relevance
“…Radio Type III bursts were also often associated with surges, suggesting that surges followed open magnetic field lines or very large loops (Chiuderi-Drago et al, 1986;Kundu et al, 1995). This idea has been confirmed by using NLFFF extrapolation showing how nonthermal types III associated with jets escape along open field lines at the edge of close structures over active regions (Lu et al, 2019;Mulay et al, 2019). Schmieder et al (1983), Schmieder et al (1984) reported on the recurrence of Hα and C IV surges with a time delay between two jet ejections of 15-30 min.…”
Section: Spectroscopic Analysismentioning
confidence: 72%
“…Radio Type III bursts were also often associated with surges, suggesting that surges followed open magnetic field lines or very large loops (Chiuderi-Drago et al, 1986;Kundu et al, 1995). This idea has been confirmed by using NLFFF extrapolation showing how nonthermal types III associated with jets escape along open field lines at the edge of close structures over active regions (Lu et al, 2019;Mulay et al, 2019). Schmieder et al (1983), Schmieder et al (1984) reported on the recurrence of Hα and C IV surges with a time delay between two jet ejections of 15-30 min.…”
Section: Spectroscopic Analysismentioning
confidence: 72%
“…Group type IIIs and complex type-III-like fast-drift bursts that occur with CMEs have been claimed to originate variously from shock-accelerated electrons, unspecified "shock-associated" acceleration, or acceleration directly from the flare site (see Cane et al 1981;Kundu & Stone 1984;Dulk et al 2000;Reiner et al 2000;Gopalswamy & Makela 2010 for details). This uncertainty may be resolved with recently available high spatial, spectral, and temporal resolution imaging of type III bursts, which provide key information about reconnection sites and contribute to our understanding of particle acceleration (Chen et al 2013(Chen et al , 2018Mulay et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…For this event, type III imaging spectroscopy was used to ascertain typical electron beam speeds around 0.2c. Comparing with magnetic field extrapolations, Mulay et al (2019) found type III radio sources at the flaring site which did not appear at the expected points along magnetic field lines. There was a distinct absence of type III frequency evolution along the field that would be consistent with electron beam propagation.…”
Section: Low Frequency Burstsmentioning
confidence: 77%
“…Type IIIs are commonly associated with jets in extreme ultraviolet (EUV) and X-rays (e.g., Bain and Fletcher, 2009;Klassen et al, 2011;Krucker et al, 2011), with electron beams typically following the same path as the jet. A number of studies have analyzed type IIIs using high resolution MWA imaging spectroscopy that occurred co-temporal and co-spatially with jets observed in UV (McCauley et al, 2017;Cairns et al, 2018;Mulay et al, 2019). In all three events the type III emission showed resolved fine temporal structure, consistent with several distinct EUV jet episodes and caused by multiple electron beam injections, explained via energization within magnetic reconnection regions by Cairns et al (2018).…”
Section: Low Frequency Burstsmentioning
confidence: 99%
See 1 more Smart Citation